Extraction of chitosan from Aspergillus niger mycelium and synthesis of hydrogels for controlled release of betahistine (2015)
Chitosan was extracted from the fungus Aspergillus niger, an alternative source of chitin that is widely available as a byproduct of the industrial production of citric acid. Chitosan with deacetylation degree (DD) of 73.6% was characterized by elemental analysis, capillary viscometry (molecular weight of 1.9×105g/mol), Fourier transform infrared (FTIR), nuclear magnetic resonance (1H NMR, 13C NMR and 15N NMR) spectroscopies, differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Fungal chitosan was crosslinked with glutaraldehyde and glutaric acid to obtain hydrogels. Chitosan hydrogels were characterized by FTIR and by scanning electron microscopy (SEM), which showed that these materials have irregular, polydisperse, and interconnected pores. Kinetic studies of the release of betahistine from the swollen hydrogels showed a Fickian diffusion mechanism. Finally, hydrolytic degradation of chitosan hydrogels under simulated physiological conditions (pH 7.4 and 37°C) was investigated as well as in vivo biocompatibility tests using New Zealand white rabbits as animal models.